2001
DOI: 10.1093/pubmed/23.4.262
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in antidepressant prescribing in the UK, 1975-1998

Abstract: Antidepressant prescribing has increased in all age and sex groups. This indicates either that there have been changes in the presentation, recognition and management of depression in general practice or that the prevalence of depression has increased, or a combination of these two phenomena. The higher prescribing rate in females is in keeping with evidence from psychiatric morbidity surveys suggesting that women experience higher levels of psychiatric morbidity than men. Decreases in the ratio of female to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 17 publications
6
90
1
5
Order By: Relevance
“…6,7 Previous studies have found few reasons to explain this general rise other than an increase in the proportion of patients receiving long-term treatment with repeat prescriptions. 8,9 The lack of impact of IAPT on antidepressant prescribing at a population level is supported by several studies.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Previous studies have found few reasons to explain this general rise other than an increase in the proportion of patients receiving long-term treatment with repeat prescriptions. 8,9 The lack of impact of IAPT on antidepressant prescribing at a population level is supported by several studies.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…5 Antidepressant prescribing has been increasing in England since the 1970s. 6,7 The reasons for this are not fully understood, but there is no evidence for increased incidence, prevalence, care-seeking behaviour or GP identification of depression. 8 One possible explanation is an increase in the proportion of patients receiving long-term treatment with repeat prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Munoz-Arroyo et al found no increase in the incidence or prevalence of depression, care-seeking behaviour by patients, or identification by GPs to account for the rise in prescription rates. 4 Suspicion exists, both in the media and in healthcare policy circles, that GPs may be prescribing antidepressants inappropriately.…”
Section: Introductionmentioning
confidence: 99%
“…Classical prototypal antipsychotics, such as chlorpromazine and haloperidol, have been replaced with atypical antipsychotic drugs for the treatment of psychotic patients. As for the pharmacotherapy for mood disorders, total antidepressant prescribing has increased, especially in 1990s with exponential increase in prescriptions of SSRIs (Donoghue, 1998;Middleton, et al, 2001). This remarkable rise in SSRIs prescribing experienced in the United Kingdom may be attributable, in part, to the Defeat Depression Campaign (Paykel et al, 1997), which was undertaken from 1992 to 1996.…”
Section: Discussionmentioning
confidence: 99%